Increases in placental nitric oxide, but not nitric oxide-mediated relaxation, underlie the improvement in placental efficiency and antihypertensive effects of hydrogen sulphide donor in hypertensive pregnancy - Possomato-Vieira, Jose S. [UNESP]; Chimini, Jessica S. [UNESP]; da Silva, Maria L. S. [UNESP]; Dias-Junior, Carlos A. [UNESP] (Wiley, 2018)
Dysregulation of hydrogen sulphide (H2S) producing enzymes has been related to hypertensive pregnancy, and H2S donor, sodium hydrosulphide (NaHS) exerts antihypertensive effects, modulates angiogenic factors production and acts as an antioxidant. Moreover, reduction in nitric oxide (NO) bioavailability is related to hypertensive pregnancy and H2S may interact with NO, modulating its production. We aimed to investigate the NaHS effects in hypertension-in-pregnancy and also in feto-placental parameters. Female Wistar rats (200-250 g) were mated and desoxycorticosterone acetate injections followed by replacement of water by 0.9% saline solution were used to induce hypertensive pregnancy. Rats were divided into four groups: normal pregnant (Norm-Preg), pregnant + NaHS (Preg+NaHS), hypertensive pregnant (HTN-Preg) and HTN-Preg+NaHS. Systolic blood pressure was increased in HTN-Preg and this increase was blunted in HTN-Preg+NaHS. Fetal and placental weights were decreased in HTN-Preg animals, while fetal growth restriction was improved in HTN-Preg+NaHS. Placental weight was lower in HTN-Preg+NaHS than in HTN-Preg; however, placental efficiency was re-established in HTN-Preg+NaHS rats. We observed that a partial contribution of placental NO, but not changes in anti-angiogenic factors may mediate the increases in placental efficiency in HTN-Preg+NaHS. HTN-Preg presented thoracic aorta hyperreactivity to phenylephrine while NaHS treatment blunted this hyperreactivity, which seems not to be related to NO-mediated relaxation induced by acetylcholine. Therefore, changes in vascular responsiveness promoted by NaHS treatment may underlie the beneficial effects in systolic blood pressure and feto-placental parameters in our study.
Keywords: hydrogen sulphide; hypertenstion in pregnancy; nitric oxide; vascular reactivity